PENGARUH AKTIVITAS SENAM OTAK (BRAIN GYM) UNTUK MENINGKATKAN KOGNITIF AUD - I Gd. Arya Wiradnyana; Kt. Arya Surasena (Widyacarya: Jurnal Pendidikan, Agama dan Budaya, 2020)
This study aims to determine the effect of brain exercise on cognitive children in EkaDharma Singaraja Kindergarten. This type of research is quasi-experimental using the designof one group pretest and posttest design. The sample in this study were 21 students in EkaDharma Singaraja Kindergarten, consisting of 13 female students and 8 male students. Thedata in this study were collected using an observation sheet instrument to see the achievementsof children's cognitive development through brain gym activities. Data collected was analyzedusing the Wilcoxon statistical test. The results of this study found that: (1) cognitive childrenbefore being given brain gymnastic activity showed that as many as 66% of cognitive categorizedchildren had not developed, 23% were categorized as developing, and 11% of students developedaccording to expectations. (2) cognitive children after being given brain gymnastic activity showedthat as many as 76% categorized as starting to develop and 24% developing students accordingto expectations, (3) the results of data analysis performed by the Wilcoxon test showed that thep value = 0.00 (< 0.05). This means there is a significant difference between children's cognitivebefore brain exercises and after being given brain exercises in the Eka Dharma Kindergarten.